International Relations of Riga Technical University and Dresden University of Technology Over Three Centuries (1862–2024) - Zigmunde, Alīda; Tipāns, Igors (History of Engineering Sciences and Institutions of Higher Education, 2024)
The cooperation between Riga Technical University (RTU) and Dresden University of Technology (TUD; Technische Universität Dresden) is one of the oldest international partnerships in the history of both universities. It started more than a century and a half ago and continues today. The cooperation between the two universities has manifested itself in various ways – both by taking over the experience of the university as an institution and sharing it, and in student and lecturer exchange trips. Some engineers and lecturers have worked at the Technical University in Riga, while former residents of Riga have studied and worked in Dresden. Cooperation agreements between the two universities were concluded in the second half of the 20th century. The best students of the renovated Riga Polytechnic Institute (RPI) continued their studies in Dresden and practiced in German companies. Both students and teaching staff went to TUD to exchange experiences. The long-term cooperation continues even today, including mutual congratulations on the anniversaries of universities and nominating scientists as Honorary Members of universities.